Security and development in India's northeast - Das, Gurudas (New Delhi ; Oxford : Oxford University Press, 2012)
Examining the linkages between external security threats, economic underdevelopment & internal security as they have affected the northeast of India, the author argues that crossborder cooperation offers a way to break what he terms a 'conflict trap'.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Internal security -- India, Northeastern; India, Northeastern -- Politics and government